1975
DOI: 10.3109/00365517509095809
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Urine Flow, Glomerular Filtration, and Urine Solute Concentrations during Prolonged Heavy Exercise

Abstract: Serum and urine electrolytes, creatinine, and urea were determined in 21 well-trained men, aged 21-56 years, in connection with a 70-km cross-country ski race, lasting 4.39-6.52 h, leading to slight dehydration. Although the race urine flow was low, averaging 0.41 (0.1-0.9) ml/min, the average urine concentrations of urea, Na, Ca, Mg, Cl and P were markedly lower than during the preceding night, while the concentrations of K and creatinine were higher, the total of measured solutes being 621 nmol/l, compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…An increased catabolism of nitrogenous compounds occurs after exercise [37], This is supported by the rise observed in serum urea after prolonged physical activity [38]. For urinary urea, a rise in the 24-hour uri nary urea excretion has been observed dur ing and after exercise [29], However, when urine is collected for a limited period dur ing and shortly after exercise, a decrease in urinary urea excretion was observed [5], It should be noticed that the present re sults were obtained in young normal male students with apparently normal renal and liver functions. Extrapolation of these results to persons with impaired renal or liver func tion could be dangerous since the clearance of several molecules or their catabolism could be decreased, leading to raised values in the plasma for longer periods.…”
Section: Urinary Urea and Uric Acid Excretionsupporting
confidence: 52%
See 1 more Smart Citation
“…An increased catabolism of nitrogenous compounds occurs after exercise [37], This is supported by the rise observed in serum urea after prolonged physical activity [38]. For urinary urea, a rise in the 24-hour uri nary urea excretion has been observed dur ing and after exercise [29], However, when urine is collected for a limited period dur ing and shortly after exercise, a decrease in urinary urea excretion was observed [5], It should be noticed that the present re sults were obtained in young normal male students with apparently normal renal and liver functions. Extrapolation of these results to persons with impaired renal or liver func tion could be dangerous since the clearance of several molecules or their catabolism could be decreased, leading to raised values in the plasma for longer periods.…”
Section: Urinary Urea and Uric Acid Excretionsupporting
confidence: 52%
“…Best [28] has also reported that acute muscular exer cise has no effect on the 24-hour urinary cre atinine excretion. However, others have shown an increased 24-hour urinary excre tion of creatinine during this type of exercise [3,29],…”
Section: Urinary Creatinine and Creatine Excretionmentioning
confidence: 99%
“…In our study, this result was obtained during moderate exercise in the heat when subjects were dehydrated prior to the exercise, and compared to the data obtained during the same exercise performed by subjects who were euhydrated prior to the exercise. As yet, a decline in urinary concentrating ability has been shown only during heavy prolonged exercise and compared to pre-exercise data at rest (Refsum andStromme 1975, 1977;Wade and Claybaugh 1980), while moderate exercise resulted, on the contrary, in concentrated urine production Johnson 1970, 1971). Thus, our data were surprising owing to both the moderate level of exercise intensity and the increased plasma levels of the hormones involved in the conservation of water and electrolytes, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Under these conditions, exercise results in an antidiuresis, and the increased plasma AVP would be expected to produce concentrated urine via an increased reabsorption of water from the collecting duct (Poortmans 1984). However, when exercise is prolonged and sustained, it has been shown that the reduction in the urine¯ow rate is accompanied by urine dilution (Refsum andStromme 1975, 1977), which is indicative of a decrease in the renal concentrating ability, in spite of an increased plasma AVP (Wade and Claybaugh 1980). It has been suggested that the increased activation of the sympatho-adrenal system that is induced by heavy exercise is responsible for impairment of the concentrating mechanism because of its impact on glomerular aerent arteriole vasoconstriction (Wade et al 1989).…”
Section: Introductionmentioning
confidence: 96%
“…This attempt is undermined by the inconstant production of creatinine. Physical activity, 8 fever 9 and dietary intake are all capable of producing signi¢cant variations in the serum creatinine. Although raw meat contains mostly creatine and very little creatinine, exposure to high temperatures vastly increases the amount of creatinine.…”
mentioning
confidence: 99%